Endocrine and reproductive endpoints of Notothenia rossii and N. coriiceps: A baseline study for ecotoxicological monitoring in Antarctic waters - Ferreira, María Florencia; Lo Nostro, Fabiana Laura; Honji, Renato Massaaki; Ansaldo, Martin; Genovese, Griselda (Marine Pollution Bulletin)
Pollution threats Antarctica and scientists blame xenobiotics and anthropic activities. Yet little is known about their effect on Antarctic ichthyofauna. Accordingly, we investigated the endocrine system of male fish Notothenia rossii and N. coriiceps (Perciformes, Nototheniidae) collected during Austral summer. For N. rossii, hormone levels of estradiol, testosterone, and 11-ketotestosterone were higher in fish collected during March than those of January; whereas for N. coriiceps estradiol and androgens levels were higher and lower in March, respectively. Histological analysis of the testes showed an unrestricted lobular type with no pathological alterations. However, detection of vitellogenin-like in plasma and skin mucus were seen in 75% of N. coriiceps males and 7% of N. rossii males. This is the first report of mucus vitellogenin-like detection as a non-invasive biomarker of endocrine disruption in notothenioid males and settles a baseline for future studies of reproductive biology and endocrine disruption in Antarctic fishes. Fil: Ferreira, María Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Biodiversidad y Biología Experimental y Aplicada; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental. Laboratorio de Ecotoxicología Acuática; Argentina Fil: Lo Nostro, Fabiana Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Biodiversidad y Biología Experimental y Aplicada; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de ...